Production of hydrogen by autothermal reforming of biogas. (August 2017) - Rau, F.; Herrmann, A.; Krause, H.; Fino, D.; Trimis, D.
Abstract: In this paper the results of the operation of a pilot-plant with a hydrogen output of 50 Nm³/h are discussed. This plant shows the possibility of distributed production of hydrogen for the powertrains based on hydrogen. The focus of the investigations is the long-term behavior of the novel Nickel-based catalyst. This includes experimental studies of the impact of the start-up sequence on the reforming performance after the necessary activation of the catalyst. Additionally the prospective demand of hydrogen requires an analysis of the start-up time of the plant. The focus was a short start-up time without harming the catalyst.